Assessment of upstream petroleum fiscal regimes in Myanmar - Wint Thiri Swe; Nnaemeka Vincent Emodi (Journal of Risk and Financial Management, 2018)
This study aims to assess Myanmar's upstream petroleum fiscal regimes by applying comprehensive indicators to rank the level of attractiveness of Myanmar. The indicators include government take (GT), front loading index (FLI), and composite score (CS). The decision maker's attitude for GT and FLI were considered in CS linear weighting method in ranking the fiscal terms attractiveness. The results showed that Myanmar's upstream petroleum fiscal regime has low attraction compared to its competing countries from the investor's point of view, both in terms of the risk to the investor in the earlier part of the project and in terms of evaluation with or without the time value of money. Also, royalty and cost recovery were identified to have an impact on the attractiveness rank of petroleum fiscal regime in Myanmar. Therefore, Myanmar should consider improving its fiscal regimes that are not neutral-particularly, royalty, tax, profit split, and cost recovery-for a favorable investment climate.
Keywords: 330; Myanmar; petroleum fiscal regimes; upstream oil and gas; fast and intuitive method; discounted cash flow model